Applying network analysis to assess the development and sustainability of multi-sector coalitions - Tessa Heeren; Caitlin Ward; Daniel Sewell; Sato Ashida (PLoS ONE, 2022)
Background Accountable Communities of Health (ACH) models have been popularized through Center for Medicare and Medicaid Innovation (CMMI) grants, including the State Innovation Model (SIM), to encourage the development of community-based coalitions across medical, public health, and social service delivery systems. These models enhance care coordination for patients and are better equipped to address Social Determinants of Health (SDH) needs. Methods Network data was collected from participating organizations in seven ACH sites established across Iowa. The application of network analysis quantitatively characterized the relational context of the interorganizational, cross-sector networks which are foundational to achieving the ACH goal of systematic, comprehensive care. Our analysis primarily used logistic network regression modeling (LNRM) to identify network structures and characteristics of organizations that facilitate or impede sustainable connections. Results Our findings suggest that the ACH was effective at stimulating sustainable connections across sectors and disparate positions of centrality in the network. Factors associated with sustainable connections between organizations included the strength of relationships and the type of collaboration, namely data sharing and resource sharing. Leadership roles designated by the ACH structure were associated with stimulating connections during the grant, but not with sustainment. Network measures of density and transitivity, which peaked during the grant period (compared to pre- and post-grant networks), further implied possible attrition of the ACH intervention effects without incentive to maintain collaborations. Conclusions Multi-sector care coordination networks were established, but our findings suggest depreciation of ACH intervention momentum and structure without incentive to maintain collaborations beyond the three-year duration of the grant. Sustainability could be bolstered and ACH goals actualized with reliable long-term funding.